Why did Kazan diocese have no archbishop in 1574–1575? (some notes on the history of Church governance in Russia in the 16th century) - Andrei Usachev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article deals with the reasons of the absence of the Kazan archbishop, the head of one of the most huge dioceses in the Russian Church in the 16th century, which took the third place in the church hierarchy. It was turned out that probably because of the state of health in February of 1574 archbishop Lavrentii (1568–1574) left it. Earlier he was the abbot of the Volotskii Monastery of St. Josef. Gurii (Rugotin) (1555–1563), German (Sadyrev-Polev) (1564–1567), the Kazan archbishops were also from the Volotskii Monastery of St. Josef. It was impossible to appoint the abbot of the Volotskii Monastery of St. Josef Tikhon (Khvorostinin) (1573–1575) or another one from this monastery to this position in 1574 because of the harmful consequences of the epidemics of 1560-1570s. The Volotskii Monastery and such large monasteries like Trinity-St. Sergius Monastery, the Simonov Monastery etc. lost the significant number of experienced monks prepared for the governing of monasteries and dioceses. Because of the domination of the meritocratical principles in the selection of candidates there were no chances to do something with the lack of prepared monks in a relatively short time. That’s why the authorities in the last third of the 16th century appointed the representatives of less famous monasteries such as the Mahrishchskii Monastery, the Starickii Monastery of Assumption, the Gerasimov Boldin Monastery. In the February of 1575 the representative of the Ipat'ev Monastery in Kostroma, the archbishop of the Novospasskii Monastery Vassian was appointed the head of the Kazan diocese. However he dead in May of 1575. In July of 1575 the abbot of the Volotskii Monastery of St. Josef Tikhon (Khvorostinin) was appointed the head of the Kazan diocese. It was possible because of the personal interference o Ivan IV. He arrived at the Volotskii Monastery of St. Josef and in fact appointed Evfimii (Turkov) (who had denied to become the abbot in 1573) the successor of Tikhon. The research rests on the materials of acts, records of income and expenses, records of donations of the Volotskii Monastery of St. Josef and another monasteries.